A fractal model for real gas transport in porous shale. Issue 4 (2nd October 2016) - Geng, Lidong; Li, Gensheng; Tian, Shouceng; Sheng, Mao; Ren, Wenxi; Zitha, Pacelli
Abstract : A model for real gas flow in shale gas matrices is proposed and consists of two main steps: (a) developing a microscopic (single pore) model for a real gas flow by generalizing our previously reported Extended Navier‐Stokes Equations (ENSE) method and (b) by using fractal theory concepts, up‐scaling the single pore model to the macroscopic scale. A prominent feature of the up‐scaled model is a predictor for the apparent permeability (AP). Both models are successfully validated with experimental data. The impact of the deviation of the gas behavior from ideality (real gas effect) on the gas transport mechanisms is investigated. The effect of the structural parameters (porosity Ф, the maximum pore diameter Dmax, and the minimum pore diameter Dmin ) of the shale matrix on the apparent permeability is studied and a sensitivity analysis is performed to evaluate the significance of the parameters for gas transport. We find that (1) the real gas transport models for a single pore and porous shale matrix are both reliable and reasonable; (2) the real gas effect affects the thermodynamic parameters of the free gas and the adsorption and transport capacity of the adsorbed gas; (3) the real gas effect decreases the effective permeability for convective flow and surface diffusion; i.e., the derivation degree of the effective permeability for bulk diffusion and Knudsen diffusion increases with increasing pressure but presents a bathtub shape when the pore diameter is smaller than 10 nm; and (4) the apparent permeability increases with Ф, Dmax, and Dmin . It is more sensitive to Dmax, followed by the porosity. Dmin has a minor impact. © 2016 American Institute of Chemical Engineers AIChE J, 63: 1430–1440, 2017